Multifunctional polymer-capped mesoporous silica nanoparticles for pH-responsive targeted drug delivery12. Issue 17 (13th April 2015) - Niedermayer, Stefan; Weiss, Veronika; Herrmann, Annika; Schmidt, Alexandra; Datz, Stefan; Müller, Katharina; Wagner, Ernst; Bein, Thomas; Bräuchle, Christoph
Abstract : Poly(2-vinylpyridine)-capped mesoporous silica nanoparticles (MSNs) for targeted triggered release by the cell-internal change in pH, as is demonstrated by in vial and in vitro experiments. Abstract : A highly stable modular platform, based on the sequential covalent attachment of different functionalities to the surface of core–shell mesoporous silica nanoparticles (MSNs) for targeted drug delivery is presented. A reversible pH-responsive cap system based on covalently attached poly(2-vinylpyridine) (PVP) was developed as drug release mechanism. Our platform offers (i) tuneable interactions and release kinetics with the cargo drug in the mesopores based on chemically orthogonal core–shell design, (ii) an extremely robust and reversible closure and release mechanism based on endosomal acidification of the covalently attached PVP polymer block, (iii) high colloidal stability due to a covalently coupled PEG shell, and (iv) the ability to covalently attach a wide variety of dyes, targeting ligands and other functionalities at the outer periphery of the PEG shell. The functionality of the system was demonstrated in several cell studies, showing pH-triggered release in the endosome, light-triggered endosomal escape with an on-board photosensitizer, and efficient folic acid–based cell targeting.